miR-155: An Important Role in Inflammation Response - Jingyan Hu; Songli Huang; Xiaoli Liu; Yuan Zhang; Shengli Wei; Xiuhua Hu (Journal of Immunology Research)
MicroRNAs (miRNAs) are a class of small, mature, noncoding RNA that lead to posttranscriptional gene silencing to regulate gene expression. miRNAs are instrumental in biological processes such as cell development, cell differentiation, cell proliferation, and cell apoptosis. The miRNA-mediated gene silencing is an important part of the regulation of gene expression in many kinds of diseases. miR-155, one of the best-characterized miRNAs, has been found to be closely related to physiological and pathological processes. What is more, miR-155 can be used as a potential therapeutic target for inflammatory diseases. We analyze the articles about miR-155 for nearly five years, review the advanced study on the function of miR-155 in different inflammatory cells like T cells, B cells, DCs, and macrophages, and then summarize the biological functions of miR-155 in different inflammatory cells. The widespread involvement of miR-155 in human diseases has led to a novel therapeutic approach between Chinese and Western medicine.